CIVIL LAW ASPECTS OF DEVELOPER’S LIABILITY OF INDIVIDUAL INVESTORS - Brovchebko, Tetiana; Bilokin, Dmytro (SWorldJournal, 2025)
This article examines the civil liability of developers towards individual investors in the field of residential construction. The relevance of the research arises from the increasing number of legal disputes caused by economic instability and the legal u